2019
DOI: 10.1259/bjr.20190117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in molecular radiotherapy—Tribulations and Triumphs Report of the NCRI CTRad meeting held at the Lift Islington, 8 June 2018

Abstract: It has been almost a decade since the commentary Molecular radiotherapy — the radionuclide raffle? by Gaze and Flux (2010). The overarching feeling then was that no individual or organisation has taken up the challenge, nationally or internationally, of championing molecular targeted radionuclide therapy in all its aspects. Here, we report on the recent NCRI–CTRad (Clinical Trials in Molecular Radiotherapy–Tribulations and Triumphs) meeting, held in London on the 8 June 2018. The meeting was organized by the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Multicentre trials will be key to enabling harmonisation of dosimetry methods between centres to produce accurate reproducible results that will build on the clinical evidence of the benefits of dosimetry in MRT. Although it has been shown that relationships have been established between absorbed dose and response, the evidence from these multicentre trials will increase this evidence base and hopefully generate more confidence in dosimetry guided MRT (Benau et al 1962, Leeper 1973, Maxon et al 1983, Lau et al 1994, Ho et al 1997, Gulec et al 2007, Lee et al 2008, Klubo-Gwiezdzinska et al 2011, Garin et al 2012, Gaze et al 2013, Mazzaferro et al 2013, Lam et al 2013, Perros et al 2014, Strigari et al 2014, Ilan et al 2015, Demirelli et al 2015, Chiesa et al 2015, Wierts et al 2016, van den Hoven et al 2016, Manceau et al 2018, Chan et al 2018, Falzone et al 2019. This report has shown that numerous guidelines are available for all different forms of dosimetry calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Multicentre trials will be key to enabling harmonisation of dosimetry methods between centres to produce accurate reproducible results that will build on the clinical evidence of the benefits of dosimetry in MRT. Although it has been shown that relationships have been established between absorbed dose and response, the evidence from these multicentre trials will increase this evidence base and hopefully generate more confidence in dosimetry guided MRT (Benau et al 1962, Leeper 1973, Maxon et al 1983, Lau et al 1994, Ho et al 1997, Gulec et al 2007, Lee et al 2008, Klubo-Gwiezdzinska et al 2011, Garin et al 2012, Gaze et al 2013, Mazzaferro et al 2013, Lam et al 2013, Perros et al 2014, Strigari et al 2014, Ilan et al 2015, Demirelli et al 2015, Chiesa et al 2015, Wierts et al 2016, van den Hoven et al 2016, Manceau et al 2018, Chan et al 2018, Falzone et al 2019. This report has shown that numerous guidelines are available for all different forms of dosimetry calculations.…”
Section: Discussionmentioning
confidence: 99%